2013
DOI: 10.1080/13574809.2012.683403
|View full text |Cite
|
Sign up to set email alerts
|

The Burdens of Place: A Socio-economic and Ethnic/Racial Exploration into Urban Form, Accessibility and Travel Behaviour in the Lansing Capital Region, Michigan

Abstract: The paper examines the relationship between urban form, socio-economic status, ethnicity, accessibility and pedestrian activity in the Lansing Capital Region, Michigan. This research explores the burdens of urban environments through a study of accessibility and travel behaviour in an urban region characterized by rapid suburbanization and urban decline. Specifically, the study seeks to answer how socio-economic and ethnic status affect accessibility and travel behaviour in urban environments that have traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Our findings correspond to existing U.S. research that shows the highest prevalence of obesity among the poor (Morland et al, 2006;Wang et al, 2007). In addition, the Detroit research is also consistent with health studies that have focused specifically on minority populations and the poor in high-density urban neighborhoods, where health outcomes (including higher BMI values) are closely linked to poverty and minority populations, regardless of built environment and design characteristics (Krieger, 2000;Scott et al, 2009;Williams, 2005;Vojnovic et al, 2013). The scale of study and distinguishing by population subgroups thus emerge as critical in linking BMI values with characteristics of the urban built environment.…”
Section: Commentary and Conclusionmentioning
confidence: 58%
See 2 more Smart Citations
“…Our findings correspond to existing U.S. research that shows the highest prevalence of obesity among the poor (Morland et al, 2006;Wang et al, 2007). In addition, the Detroit research is also consistent with health studies that have focused specifically on minority populations and the poor in high-density urban neighborhoods, where health outcomes (including higher BMI values) are closely linked to poverty and minority populations, regardless of built environment and design characteristics (Krieger, 2000;Scott et al, 2009;Williams, 2005;Vojnovic et al, 2013). The scale of study and distinguishing by population subgroups thus emerge as critical in linking BMI values with characteristics of the urban built environment.…”
Section: Commentary and Conclusionmentioning
confidence: 58%
“…However, one should not necessarily expect that this shopping behavior will be replicated in other U.S., or even Michigan cities. In a recent Lansing, Michigan study, Vojnovic and colleagues () showed that lower‐income Lansing respondents relied on convenience stores for over 35% of food shopping trips, over 3.5 times more on average than the Detroit respondents. This emphasizes, again, the need for more neighborhood‐scale access and travel behavior analyses in communities experiencing disinvestment and decline across the United States.…”
Section: Commentary and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the desire for cultural amenities, entertainment and other facilities in central cities by an in ux of employees and tourists led to the increase in sit-down restaurants in the inner city, as seen in evidence from New York, NY [44], Houston, TX [45], Washington, DC [46], and metropolitan areas [47]. During our study period, U.S. inner cities transitioned from goods production sectors toward relatively place-bound service sector industries [27,33], which includes restaurants [34,35]. Lester et al [35] observed that, in twenty U.S. inner cities between 1990 and 2000, jobs in retail services replaced jobs lost in goods-producing industries.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies suggested that sit-down restaurants tend to be located in high density neighborhoods because of walkability and the cozy atmosphere offered by urban environments [29,30]. Owners of sitdown restaurants and supermarkets as basic amenities may be disinclined to locate in Black or poor neighborhoods [30][31][32][33][34] because of uncertainty in investing in such neighborhoods. In addition, highly restrictive land use such as single-family housing may attract tra c or generate noise and high crime rate [35].…”
Section: Covariatesmentioning
confidence: 99%